Chemical approaches to detect and analyze protein sulfenic acids. Issue 2 (17th September 2013) - Furdui, Cristina M.; Poole, Leslie B.; Allan Butterfield, D.; Dalle‐Donne, Isabella
Abstract Orchestration of many processes relying on intracellular signal transduction is recognized to require the generation of hydrogen peroxide as a second messenger, yet relatively few molecular details of how this oxidant acts to regulate protein function are currently understood. This review describes emerging chemical tools and approaches that can be applied to study protein oxidation in biological systems, with a particular emphasis on a key player in protein redox regulation, cysteine sulfenic acid. While sulfenic acids (within purified proteins or simple mixtures) are detectable by physical approaches like X‐ray crystallography, nuclear magnetic resonance and mass spectrometry, the propensity of these moieties to undergo further modification in complex biological systems has necessitated the development of chemical probes, reporter groups and analytical approaches to allow for their selective detection and quantification. Provided is an overview of techniques that are currently available for the study of sulfenic acids, and some of the biologically meaningful data that have been collected using such approaches. © 2013 Wiley Periodicals, Inc. Rapid Commun. © 2013 Wiley Periodicals, Inc. Mass Spec Rev 33: 126–146, 2014.